Help to go: T cells transfer CD40L to antigen‐presenting B cells. Issue 1 (22nd December 2016) - Dustin, Michael L.
Abstract : This commentary discusses an EJI article which suggests a new, hybrid mechanism for Th1‐cell delivery of help to B cells, based on contact‐dependent CD40L transfer. The transfer process is cell contact dependent and antigen dependent. CD40 expression is required on the B‐cell surface to capture the CD40L presented by the Th1 cell. Abstract : Most immune cell communication takes place by intercellular transfer of cytokines or the contact‐dependent interaction of surface receptors in immunological synapses. In this issue of the European Journal of Immunology, Gardell and Parker ( Eur. J. Immunol . 2017, 47, 41–50) point to a new, hybrid mechanism for Th1‐cell delivery of help to B cells, based on contact‐dependent CD40L transfer. The transfer process and its specificity are both cell contact dependent and antigen dependent. CD40 expression is also required on the B‐cell surface to capture the CD40L presented by the Th1 cell. While further studies are needed to confirm the phenomenon in vivo and to test the role of transferred CD40L in other aspects of T‐cell help, this study provides an exceptional take‐off point and makes excellent use of mouse genetics to work out some possible rules for B cells being able to order help 'to go'.